Heat Transfer Experiments on Electric Aircraft Battery Minichannels with Ethylene Glycol-Air Fluid - Marausna, Gaguk; A, Dhawysulthan M; Sitepu, Eric Leonardo; Kusuma, Muhamad Bayu Adi (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2022)
The  aviation  industry  has  changed  the  mass  and  private  transportation  industry,  thus  making  aircraft more and more varied, this type of air transportation has a very high adverse effect on the atmosphere because of its very high fuel consumption and emitting so many pollutants that aircraft for the future will lead There are 2 types of aircraft, namely Hybrid-Electric Aircraft and All-Electric Aircraft. Both have the same electric power drive, but there are weaknesses in this transportation. Namely on the battery used. In general, the battery used is Lithium-ion.  Lithium-ion  has  the  characteristics  of  being  lightweight  and  more  durable  than  the  others.  The battery  itself  also  has  a  weakness,  if it is  used  for  too long or  continuously  the  battery  will  heat  up  and  reduce battery life.  Therefore, cooling  the  battery is  also  needed  to  reduce  battery heat  and  maintain  battery life.  The results obtained in this study are the use of working fluid 75% Ethylene Glycol –25% Water is better than 75% Water –25% Ethylene Glycol.